2019
DOI: 10.3847/1538-3881/ab0cf7
|View full text |Cite
|
Sign up to set email alerts
|

RAMSES II: RAMan Search for Extragalactic Symbiotic Stars Project Concept, Commissioning, and Early Results from the Science Verification Phase

Abstract: Symbiotic stars (SySts) are long-period interacting binaries composed of a hot compact star, an evolved giant star, and a tangled network of gas and dust nebulae. They represent unique laboratories for studying a variety of important astrophysical problems, and have also been proposed as possible progenitors of SNIa. Presently, we know 257 SySts in the Milky Way and 69 in external galaxies. However, these numbers are still in striking contrast with the predicted population of SySts in our Galaxy. Because of ot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Searches for SySt in external galaxies have steadily progressed over the years (Gonc ¸alves et al 2008(Gonc ¸alves et al , 2012(Gonc ¸alves et al , 2015Kniazev et al 2009;Angeloni et al 2014;Mikołajewska, Caldwell & Shara 2014;Mikołajewska et al 2017;Roth et al 2018;Drozd et al 2019), and the current total of known extragalactic SySt amounts to ∼70 systems (Akras et al 2019;Chen, Liu & Shan 2019;Merc, Gális & Wolf 2019b). New surveys aiming to SySt within the Local Group (Angeloni et al 2019) promise to increase such numbers, especially for the burn-SySt type.…”
Section: The New Syst Probed By Galahmentioning
confidence: 99%
“…Searches for SySt in external galaxies have steadily progressed over the years (Gonc ¸alves et al 2008(Gonc ¸alves et al , 2012(Gonc ¸alves et al , 2015Kniazev et al 2009;Angeloni et al 2014;Mikołajewska, Caldwell & Shara 2014;Mikołajewska et al 2017;Roth et al 2018;Drozd et al 2019), and the current total of known extragalactic SySt amounts to ∼70 systems (Akras et al 2019;Chen, Liu & Shan 2019;Merc, Gális & Wolf 2019b). New surveys aiming to SySt within the Local Group (Angeloni et al 2019) promise to increase such numbers, especially for the burn-SySt type.…”
Section: The New Syst Probed By Galahmentioning
confidence: 99%
“…Seven of them satisfy the new IR selection criterion of SySts (ii). Two of these seven candidates, Hen 3-1768 and GSC 09276-00130, were observed during the verification tests of the RAMSES-II project (Angeloni et al 2019) and a Raman-scattered O 𝜆6830 line excess was reported for both objects. Follow-up spectroscopic observation of Hen 3-1768 shows clearly the presence of the O , He and H 𝛼 emission lines (Lucy et al 2018).…”
Section: Resultsmentioning
confidence: 94%
“…Follow-up spectroscopic observation of Hen 3-1768 shows clearly the presence of the O , He and H 𝛼 emission lines (Lucy et al 2018). GSC 09276-00130, on the other hand, was found to be an M-type giant (Angeloni et al 2019), without satisfy the IR criterion from the SySts/K-giant/M-giant model (iii). This result demonstrates that the additional criteriin from the SySts/K-giant/M-giant model can further distinguish single K-and M-type giants from SySts.…”
Section: Resultsmentioning
confidence: 99%
“…These features are observed almost exclusively in symbiotic binaries, and in the Milky Way the presence of the Raman scattered lines is confirmed in about 55% of the symbiotic population; in the SMC the percentage is 92% (Akras et al 2019). Future surveys focusing on these Raman features, like the RAMSES II search (Angeloni et al 2019), can shed more light on the true population of symbiotic binaries and therefore provide some constraints on the birthrates of SNe Ia and AICs from the symbiotic channel.…”
Section: Lin 358 In the Context Of The Origin Of Sn Iamentioning
confidence: 91%